Caso de estudio: exportación al Reino Unido de vodka hecho con papa peruana - Berrocal Costa, Ana Lucía (2021)
The present research work aims to determine the viability of the exportation of Peruvian potato-based vodka to the British market, specifically, to the city of London. Hence, this place was selected according to the factor ranking methodology that compared it with countries such as the United States, France, Germany and Russia. Likewise, the main trends of the British market with respect to the alcoholic beverages industry, especially vodka, and the characteristics of the consumers were evaluated. It should be noted that, for the purposes of this work, secondary sources from renowned authors such as Euromonitor International, World Bank, TradeMap, Promperú, Trade Helpdesk, among others, were used. Now, the start of operations of a company called Wak'a was assumed, which, in addition to making vodka for export, represents the solution to a national problem: the lack of competitiveness of the Peruvian potato. The research was developed from a commercial approach, drawing up an international marketing and commercialization plan. For this, it was considered the best alternative to sell through a distributor, since he knows and manages a commercial network, reduces risks and, especially, allows time and money resources to be used efficiently. Although the viability of the business was verified, through qualitative and quantitative methods, it is advisable to apply a market study to select the best commercial strategies for the short and long term.